(untitled) (Journal of the College of Basic Education, 2025)
Abstract:The research aimed to identify the level of health culture of young people and the extent of their knowledge of the use of stimulants, hormonal drugs and harmful nutritional supplements, and the physical, psychological and social consequences and damage that result from abuse, and to identify the motives behind the use of stimulants, hormonal drugs and harmful nutritional supplements among young people. The researchers used the descriptive survey method in order to suit the nature of the research. The research community was determined from (sports hall patrons) in different areas of Baghdad Governorate for the year (2024). The research sample was chosen randomly, and the sample was divided into two samples based on the requirements of the study, so that the exploratory sample was (30) participants distributed among (3) halls, with each hall having (10) participants, in a random manner. As for the application sample, the total sample was (240), represented by (12) sports halls in Al-Karkh and (12) halls in Al-Rusafa. The sample was selected so that participants had been participating for more than six months. In light of the results obtained, the researchers concluded that the majority of athletes have a positive tendency toward taking performance enhancers, and a significant deficiency in the cognitive and scientific aspects and the health, psychological, and social effects caused by performance enhancers, as well as the absence of health awareness and sports culture in sports institutions to deal with the athletes’ communities of these. The category, the weakness of health control and careful laboratory examination of these materials, and the intensity of their entry and importation from profitable commercial companies. The researchers recommend the need for concerned parties to pay attention to setting a future vision for health oversight of performance enhancers and holding periodic programs to educate and guide young athletes, increase their knowledge of performance enhancers, and educate them about their physical, psychological, social, and legal consequences and harms, while emphasizing that these harms and risks appear later and are lost with all the quick gains that occur.